2013
DOI: 10.2466/10.21.cp.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress in early motherhood: stress spillover and social support1

Abstract: Mothers facing stressors or lacking adequate support often fi nd parenting more challenging and less enjoyable. This study examined the mechanisms through which contextual variables might infl uence perceptions of parenting. Participants were 153 mothers of toddlers who completed interviews and questionnaires on life adversity, social support, negative aff ect, and parenting stress. Life adversity was positively associated with parenting stress and this association was mediated through negative aff ect. Emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…Social support also has been found to have particular benefits for those experiencing stressful life events or other significant challenges (Alloway & Bebbington, 1987;Barrera, 1986;Cohen & Wills, 1985;Lee et al, 2011;Maguire-Jack & Wang, 2016;Parkes & Sweeting, 2018;Schoefield et al, 2012). Additionally, research has found that social support is beneficial to mothers who experience the increased caretaking demands of early childhood (Arikan et al, 2019;Green et al, 2011) or parenting stress associated with raising a child with challenging behavior (BeLue et al, 2015;Cherry et al, 2019;Heberle et al, 2015;Huang et al, 2014;Maguire-Jack & Wang, 2016;Williamson et al, 2013). Therefore, social support may serve as an important family resource that buffers the effect of stress on parent functioning.…”
Section: Family Stress Theory and The Bioecological Model Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support also has been found to have particular benefits for those experiencing stressful life events or other significant challenges (Alloway & Bebbington, 1987;Barrera, 1986;Cohen & Wills, 1985;Lee et al, 2011;Maguire-Jack & Wang, 2016;Parkes & Sweeting, 2018;Schoefield et al, 2012). Additionally, research has found that social support is beneficial to mothers who experience the increased caretaking demands of early childhood (Arikan et al, 2019;Green et al, 2011) or parenting stress associated with raising a child with challenging behavior (BeLue et al, 2015;Cherry et al, 2019;Heberle et al, 2015;Huang et al, 2014;Maguire-Jack & Wang, 2016;Williamson et al, 2013). Therefore, social support may serve as an important family resource that buffers the effect of stress on parent functioning.…”
Section: Family Stress Theory and The Bioecological Model Of Developmentmentioning
confidence: 99%
“…The toddler years are a developmental period associated with increases in externalizing behaviors, such as tantrums, aggression, and oppositional behavior (Alink et al, 2006;Holtz et al, 2015;Williamson et al, 2013). Although normative, these increases in behavior problems present daily challenges that may lead to increases in parental stress.…”
mentioning
confidence: 99%
“…Becoming a parent before one achieves maturity is one of the most difficult experiences for young people, especially for girls, who shoulder the greatest consequences of early motherhood (Mikołajczyk-Lerman, 2007). To teenagers, pregnancy almost always comes as a surprise bordering on shock -an event for which they are completely psychologically unprepared (Kościelska, 1998;Williamson et al, 2013). Then comes the fear of one's own future and concern about the parents' reaction.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the psychological aspect of teenage motherhood, we should point out that young girls are under the burden of two stressful crisesadolescence and pregnancy. This problematic situation renders teenage mothers much more vulnerable to physical and psychological stress-related disorders (Christ et al, 1990;Conger et al, 1984;Garcia Coll et al, 1987;Leese, 2016;Mikołajczyk-Lerman, 2007;Williamson et al, 2013). Support coming from mothers and life partners significantly reduces the difficulties (Gee & Rhodes, 2003), and teenagers begin to feel competent (Bidzan & Redzimska, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation